2015
DOI: 10.1093/chemse/bjv077
|View full text |Cite
|
Sign up to set email alerts
|

Sternal Gland Scent-Marking Signals Sex, Age, Rank, and Group Identity in Captive Mandrills

Abstract: Mandrills are one of the few Old World primates to show scent-marking. We combined ethological and chemical approaches to improve our understanding of this behavior in 3 zoo-managed groups. We observed the olfactory behavior performed by adults and adolescents (N = 39) for 775h. We investigated the volatile components of sternal scent-marks using gas chromatography-mass spectrometry and compared volatile profiles with traits of the signaler. Males marked more than females and within each sex the frequency of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 61 publications
2
61
0
Order By: Relevance
“…Identifying whether or not chemo‐sensory signals/cues differ between groups of interest is a major component of GC‐MS research . From simulation study 1, we found that when differences between groups were pronounced, and the structure of the underlying data was relatively simple, all methods resulted in comparable model performance.…”
Section: Classification Accuracy Is Related To Data Normalizationmentioning
confidence: 98%
See 1 more Smart Citation
“…Identifying whether or not chemo‐sensory signals/cues differ between groups of interest is a major component of GC‐MS research . From simulation study 1, we found that when differences between groups were pronounced, and the structure of the underlying data was relatively simple, all methods resulted in comparable model performance.…”
Section: Classification Accuracy Is Related To Data Normalizationmentioning
confidence: 98%
“…Information in these ‘odors’ can be encoded either digitally through the presence/absence of individual compounds, and/or analogically through their relative abundance . Their composition varies with primary gland products, secondary metabolites from commensal microbiota, and environmental factors, and can therefore convey a wide range of individual‐specific information such as age, sex, diet, disease status, reproductive state, and genotype …”
Section: Introductionmentioning
confidence: 99%
“…Chemical signals are excreted in saliva, urine, feces, or from sternal, anogenital, subcaudal, or cutaneous scent glands, frequently through scent‐marking behavior (Drea, 2015; Zhang et al, 2009). Chemical signals may relay information about individual identity, age, sex, hormonal condition, genetic quality, immune function, and/or social status, although studies suggest that the informational content likely differs by species (e.g., Charpentier, Boulet, & Drea, 2008; Epple, Golob, Cebul, & Smith III, 1981; Hayes, Morelli, & Wright, 2004; Vaglio et al, 2015). Because scent is a longer‐lasting form of communication, these signals have the potential to provide information to unwanted receivers who pass by later, such as predators (that can use scent marks to track prey) or rival conspecifics (that may attempt to invade a pair's territory; Zhang et al, 2009).…”
Section: Multimodal Signaling Within Primate Pair‐bondsmentioning
confidence: 99%
“…Innocenti et al ., ), chemical properties [e.g. scent secretions (Chen & Haviland‐Jones, ; Palagi & Dapporto, ; Vaglio et al ., )] and statistical patterns [Zipf's law of abbreviation and Menzerath's law (e.g. Gustison et al ., ; Heesen et al ., )].…”
Section: Theories Of the Origins Of Languagementioning
confidence: 99%